Composition
The use of a low molecular weight polymer with aromatic monomers and polar functional groups in the adhesive composition stabilizes metal oxide particles, enhancing refractive index and transparency by preventing agglomeration.
Patent Information
- Application Number
- JP2023096519
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
AI Technical Summary
Existing adhesive compositions with metal oxide particles face challenges in achieving high refractive index and transparency due to agglomeration issues, which hinder the stabilization of these particles.
A composition containing metal oxide particles and a low molecular weight polymer with a predetermined amount of structural units derived from aromatic monomers, including polar functional groups, is used to enhance dispersion stability and improve refractive index and transparency.
The composition effectively increases the refractive index and transparency of the adhesive while maintaining good dispersion stability of metal oxide particles, even when using non-aromatic solvents.
Smart Images

Figure 2024178031000001 
Figure 2024178031000002 
Figure 2024178031000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a technique for dispersing metal oxide particles. [Background technology]
[0002] Adhesive compositions having metal oxide particles dispersed therein are known. For example, Patent Document 1 describes an adhesive having metal oxide particles dispersed in an adhesive polymer as a high refractive index transparent adhesive for appropriately bonding image display parts, light source parts, recording parts, polarizing plates, retardation plates, optical compensation films, brightness enhancing films, light diffusing films, protective films, and the like in image display devices such as liquid crystal displays (LCDs), organic EL displays, and plasma display panels (PDPs) and optical discs.
[0003] However, when dispersing metal oxide particles in an adhesive polymer, the adhesive polymer forms a structure in which the metal oxide is ionically cross-linked, which tends to cause aggregation, making it difficult to stably disperse the metal oxide particles. Patent Document 2 describes how the above problem is solved by adding a non-aromatic polymer with a weight-average molecular weight of 50,000 or less to an adhesive (meth)acrylic polymer together with the metal oxide particles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-120726 A [Patent Document 2] Patent Publication No. 2021-134322 Summary of the Invention [Problem to be solved by the invention]
[0005] However, a high refractive index transparent adhesive is required to have a further improvement in at least one of the refractive index and transparency. Accordingly, an object of the present invention is to improve at least one of the refractive index and transparency of the adhesive obtained. [Means for solving the problem]
[0006] As a result of extensive research to solve the above problems, the inventors discovered that adding a composition containing metal oxide particles and a low molecular weight polymer having a predetermined amount of structural units derived from aromatic monomers to an adhesive polymer improves the refractive index of the resulting adhesive, and that adding a composition containing metal oxide particles and a low molecular weight polymer having a polar functional group at the end of the main chain improves the transparency of the resulting adhesive, thereby completing the present invention.
[0007] The present invention, which has been able to solve the above problems, has the following configuration. [1] A composition comprising metal oxide particles (A) and a polymer (B) having a weight-average molecular weight of 50,000 or less, the polymer (B) containing 10 to 90 mass % of structural units derived from aromatic monomers. [2] The composition according to [1], wherein the refractive index of the aromatic monomer is 1.5 or more. [3] The composition according to [1] or [2], wherein the aromatic monomer is at least one monomer selected from the group consisting of aryl (meth)acrylates and aralkyl (meth)acrylates. [4] The composition according to any one of [1] to [3], wherein the polymer (B) has at least one polar functional group selected from an amino group, an amide group, a sulfo group, a carboxy group, a phosphate group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, a thiol group, an epoxy group, and an oxazoline group. [5] The composition according to any one of [1] to [4], wherein the polymer (B) further contains a structural unit derived from a low Tg (meth)acrylic acid ester such that the glass transition temperature of the homopolymer is 0° C. or lower. [6] The composition according to any one of [1] to [5], wherein the content of the metal oxide particles (A) is 100 to 400 parts by mass per 100 parts by mass of the polymer (B). [7] The composition according to any one of [1] to [6], wherein the metal oxide particles (A) have a refractive index of 2 or more. [8] The composition according to any one of [1] to [7], wherein the content of toluene and xylene in the composition is 5 mass % or less. [9] A pressure-sensitive adhesive composition comprising the composition according to any one of [1] to [8] and a pressure-sensitive adhesive (meth)acrylic polymer.
[10] A polymer composition comprising metal oxide particles (A) and a polymer (B) having a weight average molecular weight of 50,000 or less, The composition, wherein the polymer (B) is a polymer having a polar functional group at an end of the main chain.
[11] The composition according to
[10] , wherein the polar functional group is a functional group selected from a carboxyl group, a hydroxyl group, an amino group, a sulfo group, a phosphoric acid group, a phosphonic acid group, and a hydrolyzable alkoxysilyl group.
[12] The composition according to
[10] or
[11] , wherein the polymer (B) further contains a structural unit derived from a low Tg (meth)acrylic acid ester such that the glass transition temperature of the homopolymer is 0°C or lower.
[13] The composition according to any one of
[10] to
[12] , wherein the content of the metal oxide particles (A) is 100 to 400 parts by mass per 100 parts by mass of the polymer (B).
[14] The composition according to any one of
[10] to
[13] , wherein the metal oxide particles (A) have a refractive index of 2 or more.
[15] The composition according to any one of
[10] to
[14] , wherein the content of toluene and xylene in the composition is 5 mass % or less.
[16] A pressure-sensitive adhesive composition comprising the composition according to any one of
[10] to
[15] and a pressure-sensitive adhesive (meth)acrylic polymer. Effect of the Invention
[0008] By adding the composition of the present invention to an adhesive polymer, the refractive index and / or transparency of the resulting adhesive can be increased. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention encompasses a composition (hereinafter sometimes referred to as composition 1) containing metal oxide particles (A) and a polymer (B) having a weight average molecular weight of 50,000 or less, the polymer (B) containing 10 to 90 mass% of structural units derived from aromatic monomers, and a composition (hereinafter sometimes referred to as composition 2) containing metal oxide particles (A) and a polymer (B) having a weight average molecular weight of 50,000 or less, the polymer (B) being a polymer having a polar functional group at the end of the main chain. By adding composition 1 and / or composition 2 of the present invention to an adhesive polymer, the refractive index and / or transparency of the resulting adhesive can be increased. In particular, by adding composition 1 to an adhesive polymer, the refractive index (preferably the refractive index and transparency) of the resulting adhesive can be increased, and by adding composition 2 to an adhesive polymer, the transparency (preferably the refractive index and transparency) of the resulting adhesive can be increased. In this specification, composition 1 and / or composition 2 may be collectively referred to as a "dispersion composition".
[0010] The dispersion composition of the present invention is also preferable in that it has the effect of increasing the dispersion stability of the metal oxide particles (A) in the dispersion composition. When the dispersion stability of the metal oxide particles (A) in the dispersion composition is increased, the dispersion stability of the metal oxide particles (A) in the adhesive composition obtained by adding the dispersion composition to an adhesive polymer can be increased.
[0011] <Dispersion composition> [Metal oxide particles (A)] Examples of metals constituting the metal oxide particles (A) include Ti, Al, Zr, In, Zn, Sn, La, Y, Ce, Mg, Ba, Ca, etc., and from the viewpoint of increasing the refractive index, at least one selected from the group consisting of Ti, Al, Zr, Zn, Sn, and Ce is preferable, at least one selected from the group consisting of Ti, Zn, and Zr is more preferable, Ti and / or Zr is even more preferable, and Zr is particularly preferable. The metal oxide (A) may be an oxide of a single metal, a solid solution of two or more oxides, or a composite oxide. Examples of single metal oxides include aluminum oxide (Al2O3), titanium oxide (TiO2), zirconium oxide (ZrO2), indium oxide (In2O3), zinc oxide (ZnO), tin oxide (SnO2), lanthanum oxide (La2O3), yttrium oxide (Y2O3), cerium oxide (CeO2), and magnesium oxide (MgO). Examples of solid solutions of two or more oxides include indium tin oxide (ITO), antimony tin oxide (ATO), etc. Examples of composite oxides include barium titanate (BaTiO3), perovskite (CaTiO3), spinel (MgAl2O4), etc.
[0012] The metal oxide particles (A) are preferably particles having a refractive index of 2 or more, and are particularly preferably titanium oxide (TiO2), zirconium oxide (ZrO2), or zinc oxide (ZnO). Particles with a high refractive index are prone to significant deterioration in appearance when the dispersion stability is even slightly impaired, and it would be a great advantage to be able to incorporate such high refractive index particles at high concentrations while maintaining a good appearance.
[0013] The number average particle diameter of the metal oxide particles (A) is, for example, 1 to 50 nm, preferably 2 to 30 nm, and more preferably 5 to 20 nm. When the number average particle diameter of the metal oxide particles (A) is within the above range, the transparency of the obtained pressure-sensitive adhesive becomes higher.
[0014] The ratio (dv / dn) of the volume average particle diameter (dv) to the number average particle diameter (dn) of the metal oxide particles (A) is preferably 1 to 10, more preferably 5 or less, and further preferably 3 or less.
[0015] The metal oxide particles (A) may be in the form of spheres, granules, ellipsoids, cubes, rectangular parallelepipeds, pyramids, needles, columns, rods, cylinders, scales, plates, flakes, or irregular shapes, and are preferably in the form of spheres, granules, or columns from the viewpoint of dispersion stability, etc.
[0016] The metal oxide particles (A) may be previously surface-treated with a surface treatment agent. The metal oxide particles (A) are preferably surface-treated with at least one surface treatment agent selected from the group consisting of carboxylic acid compounds, silane coupling agents, and organic phosphorus compounds, and more preferably surface-treated with at least a carboxylic acid compound. The metal oxide particles (A) have a surface treatment layer formed by the surface treatment agent, which can further increase the dispersion stability in the dispersion composition or the pressure-sensitive adhesive composition.
[0017] Examples of the carboxylic acid compound include (meth)acrylic acids (e.g., (meth)acryloxy C such as acrylic acid, methacrylic acid, and 3-acryloxypropionic acid). 1-6 Alkyl carboxylic acids, etc.);C 3-9 (Meth)acryloxy group of aliphatic dicarboxylic acids C 1-6 Half esters with alkyl alcohols (e.g., 2-acryloxyethyl succinate, 2-methacryloxyethyl succinate, etc.), C 5-10 (Meth)acryloxy group of alicyclic dicarboxylic acid C 1-6 Half esters with alkyl alcohol (e.g., 2-acryloxyethylhexahydrophthalic acid, 2-methacryloxyethylhexahydrophthalic acid, etc.), C 8-14 (Meth)acryloxy group of aromatic dicarboxylic acids C 1-6Examples of suitable carboxylic acids include ester groups such as half esters of alkyl alcohols (e.g., 2-acryloxyethyl phthalate, 2-methacryloxyethyl phthalate, etc.); linear carboxylic acids having 4 to 20 carbon atoms such as butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, and stearic acid; branched carboxylic acids having 5 to 20 carbon atoms such as pivalic acid, 2,2-dimethylbutyric acid, 3,3-dimethylbutyric acid, 2,2-dimethylvaleric acid, 2,2-diethylbutyric acid, 3,3-diethylbutyric acid, 2-methylhexanoic acid, 2-ethylhexanoic acid, 3-methylhexanoic acid, 3-ethylhexanoic acid, 2-methylheptanoic acid, 4-methyloctanoic acid, and neodecanoic acid; and cyclic carboxylic acids such as naphthenic acid and cyclohexanedicarboxylic acid. 3-9 (Meth)acryloxy group of aliphatic dicarboxylic acids C 1-6 They are half esters of alkyl alcohols and branched carboxylic acids having carbon numbers of 5 to 20. These carboxylic acid compounds may be used alone or in combination of two or more kinds.
[0018] Examples of silane coupling agents include alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane and vinyltriethoxysilane; alkoxysilane compounds having an amino group, such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and N-2-(aminoethyl)-3-aminopropylmethyltrimethoxysilane; 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-methacryloxypropylmethyldimethoxysilane; Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloyl group, such as silane and 3-methacryloxypropylmethyldiethoxysilane; alkoxysilane compounds having a mercapto group, such as 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; and alkoxysilane compounds having an epoxy group, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. These silane coupling agents may be used alone or in combination of two or more.
[0019] Examples of the organic phosphorus compound include phosphate esters, phosphites, and phosphonate esters bonded to an alkyl group having 1 to 30 carbon atoms; and phosphate esters, phosphites, and phosphonate esters having a polyether chain, with phosphate esters, phosphites, and phosphonate esters having a polyether chain being preferred.
[0020] Examples of the phosphate ester, phosphite ester, and phosphonate ester having an alkyl group having 1 to 30 carbon atoms bonded thereto include compounds represented by the following formulas.
[0021] [ka]
[0022] Examples of the phosphate ester, phosphite ester, and phosphonate ester having a polyether chain include compounds represented by the following formulas.
[0023] [ka]
[0024] [ka]
[0025] In the formula, a is 1 or 2, and preferably 1. p11, p12, and p15 are each independently 4 to 15, and the total of p11, p12, and p15 is 1 to 50, and preferably 1 to 30. r1, r2, and r12 are each 1 to 20, and preferably 1 to 10. R 4 , R 5 , R 6 are each independently a divalent aliphatic hydrocarbon group having 1 to 18 carbon atoms, a divalent aromatic-containing hydrocarbon group having 6 to 30 carbon atoms, or a divalent group having 7 to 30 carbon atoms which is a combination of an aliphatic hydrocarbon group and an aromatic-containing hydrocarbon group, 4 , R 5 , R 6 When R has -CH2-, the -CH2- may be replaced with -O-. 4 , R 5 , R 6 are each independently preferably a divalent aliphatic hydrocarbon group having 1 to 18 carbon atoms, and more preferably an alkylene group having 1 to 10 carbon atoms.
[0026] Examples of the organic phosphorus compound that can be used include Newcol 1000-FCP (manufactured by Nippon Nyukazai Co., Ltd.), Antox EHD-400 (manufactured by Nippon Nyukazai Co., Ltd.), Phoslex series (manufactured by SC Organic Chemical Co., Ltd.), Light Acrylate P-1A (manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate P-1M (manufactured by Kyoeisha Chemical Co., Ltd.), TEGO (registered trademark) Dispers 651, 655, 656 (manufactured by Evonik), DISPERBYK-110, 111, 180 (manufactured by BYK Japan KK), KAYAMER PM-2, KAYAMER PM-21 (manufactured by Nippon Kayaku Co., Ltd.), and the like.
[0027] The above organic phosphorus compounds may be used alone or in combination of two or more kinds.
[0028] The amount (coating amount) of the surface treatment layer on the surface of the metal oxide particles (A) is, for example, 0 to 50 mass%, preferably 0.1 to 45 mass%, more preferably 0.5 to 40 mass%, based on 100 mass% of the entire coated particles. In particular, the amount (coating amount) of the carboxylic acid compound treatment layer on the surface of the metal oxide particle (A) is, for example, 0 to 40 mass%, preferably 1 to 35 mass%, and more preferably 5 to 30 mass%, based on 100 mass% of the entire coated particles. The amount of the silane coupling agent treatment layer (coating amount) on the surface of the metal oxide particle (A) is, for example, 0 to 30 mass%, preferably 0.1 to 20 mass%, and more preferably 1 to 15 mass%, based on 100 mass% of the entire coated particles. The amount of the organophosphorus compound treatment layer (coating amount) on the surface of the metal oxide particle (A) is, for example, 0 to 40 mass%, preferably 0.1 to 35 mass%, and more preferably 0.5 to 30 mass%, based on 100 mass% of the entire coated particles.
[0029] The amount (coating amount) of the surface treatment layer on the surface of the metal oxide particles (A) can be determined by heating the metal oxide particles (A) using a TG-DTA (thermogravimetric-differential thermal analysis) device and measuring the weight (mass) loss rate of the particles.
[0030] The amount of the metal oxide particles (A) is, for example, 5 to 60 mass %, preferably 10 to 55 mass %, and more preferably 15 to 50 mass %, based on 100 mass % of the dispersion composition. The amount of the metal oxide particles (A) is preferably 100 to 450 parts by mass, more preferably 120 to 400 parts by mass, and even more preferably 150 to 350 parts by mass, per 100 parts by mass of the polymer (B) having a weight average molecular weight of 50,000 or less, which will be described later.
[0031] [Polymer (B) with a weight-average molecular weight of 50,000 or less] The polymer (B) having a weight-average molecular weight of 50,000 or less contained in the dispersion composition of the present invention (hereinafter sometimes referred to as "low molecular weight polymer (B)") is a polymer dispersant that acts on the metal oxide particles (A) to enhance their dispersion stability. And because the molecular weight is 50,000 or less, aggregation of the polymer itself can be prevented even if it is attracted to the metal oxide particles (A) through interaction, and the metal oxide particles can be highly dispersed.
[0032] The weight average molecular weight of the low molecular weight polymer (B) is 50,000 or less, preferably 10,000 or less, more preferably 8,000 or less, and even more preferably 6,000 or less. The smaller the weight average molecular weight, the better the dispersion stability. The lower limit of the weight average molecular weight is, for example, 1,000 or more, preferably 2,000 or more, and more preferably 3,000 or more. By adjusting the weight average molecular weight to a predetermined value or more, the aggregation of the metal oxide particles (A) can be further suppressed due to the steric repulsion of the low molecular weight polymer (B).
[0033] The low molecular weight polymer (B) is preferably a polymer having a polar functional group. When the low molecular weight polymer (B) has a polar functional group, the dispersion stability of the metal oxide particles (A) in the dispersion composition or the pressure-sensitive adhesive composition can be further improved.
[0034] Examples of the polar functional group include an amino group, an amide group, a sulfo group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, a thiol group, an epoxy group, and an oxazoline group. The low molecular weight polymer (B) may have one or more polar functional groups. The low molecular weight polymer (B) may have a polar functional group in a side chain, in a main chain terminal, or in a side chain and a main chain terminal. The hydrolyzable alkoxysilyl group is preferably a silyl group having 1 to 3 methoxy or ethoxy groups bonded to a silicon atom.
[0035] The polar functional group is preferably a carboxy group, a hydroxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, a sulfo group, an amino group, or an amide group, more preferably a carboxy group, a hydroxy group, an amino group, a sulfo group, a phosphoric acid group, a phosphonic acid group, or a hydrolyzable alkoxysilyl group, still more preferably a carboxy group, a sulfo group, a phosphoric acid group, a phosphonic acid group, or a hydrolyzable alkoxysilyl group, and particularly preferably a carboxy group.
[0036] The polar functional group can be introduced into the low molecular weight polymer (B) by polymerizing the low molecular weight polymer (B) using a monomer (B1) having an adsorption site for a metal oxide described below as a polymerizable monomer and / or by polymerizing the low molecular weight polymer (B) using a chain transfer agent (B4) having a polar functional group described below.
[0037] The low molecular weight polymer (B) is a polymer obtained by polymerizing a polymerizable monomer, that is, the low molecular weight polymer (B) has a structural unit derived from a polymerizable monomer. The polymerizable monomer refers to a monomer having at least one polymerizable unsaturated group in the molecule. The polymerizable monomer includes a monomer (B1) having an adsorption site for a metal oxide, a low Tg (meth)acrylic acid ester (B2), an aromatic monomer (B3), and other monomers (P), and may be used alone or in combination of two or more kinds.
[0038] The monomer (B1) having an adsorption site for the metal oxide includes a monomer (B3) having one or more functional groups (hereinafter sometimes referred to as an adsorption group) selected from an amino group, an amide group, a sulfo group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, a thiol group, an epoxy group, and an oxazoline group, and a polymerizable unsaturated group. The hydrolyzable alkoxysilyl group is preferably a silyl group having a total of 1 to 3 methoxy groups or ethoxy groups bonded to a silicon atom. The polymerizable unsaturated group includes a (meth)acryloyl group, a vinyl group, and the like.
[0039] When the low molecular weight polymer (B) has a structural unit derived from a monomer (B1) having an adsorption site for a metal oxide, the dispersion stability of the metal oxide particles (A) in the dispersion composition or pressure-sensitive adhesive composition can be further improved.
[0040] Examples of the monomer (B1) having an amino group as an adsorptive group include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate. Examples of the monomer (B1) having an amide group as an adsorptive group include N-vinylpyrrolidone, (meth)acryloylmorpholine, (meth)acrylamide, and N-methylolacrylamide. Examples of the monomer (B1) having a sulfo group as an adsorptive group include vinyl sulfonic acid and 2-sulfoethyl (meth)acrylate. Examples of the monomer (B1) having a carboxy group as an adsorptive group include (meth)acrylic acid, itaconic acid, crotonic acid, maleic anhydride, maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl phthalic acid, and 2-(meth)acryloyloxyethyl hexahydrophthalic acid, and among these, (meth)acrylic acid is preferred. An example of the monomer (B1) having a phosphate group as an adsorptive group is 2-hydroxyethyl (meth)acryloyl phosphate. An example of the monomer (B1) having a phosphonic acid group as an adsorptive group is [3-((meth)acryloyloxy)propyl]phosphonic acid. Examples of the monomer (B1) having a hydrolyzable alkoxysilyl group as an adsorption group include vinyl alkoxysilanes such as vinyl trimethoxysilane, vinyl triethoxysilane, and dimethyl vinyl methoxysilane, and (meth) acryloxy C such as γ-(meth) acryloxypropyl trimethoxysilane and γ-(meth) acryloxypropyl methyl dimethoxysilane. 1-4 Alkylalkoxysilane and the like. An example of the monomer (B1) having an isocyanate group as an adsorptive group is 2-(meth)acryloyloxyethyl isocyanate. Examples of the monomer (B1) having a hydroxy group as an adsorbing group include (meth)acrylic acid hydroxy C such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. 1-10 Alkyl esters and the like. An example of the monomer (B1) having an epoxy group as an adsorptive group is glycidyl (meth)acrylate. Examples of the monomer (B1) having an oxazoline group as an adsorption group include 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline.
[0041] The low-molecular-weight polymer (B) may contain one or more structural units derived from a monomer (B1) having an adsorption site for a metal oxide.
[0042] As the monomer (B1) having an adsorption site for a metal oxide, a monomer (B1) having one or more adsorption groups selected from an amino group, an amide group, a sulfo group, a carboxy group, a phosphate group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, an epoxy group, and an oxazoline group is preferred, a monomer (B1) having one or more adsorption groups selected from a carboxy group, a phosphate group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, a sulfo group, an amino group, and an amide group is more preferred, and a monomer (B1) having a carboxy group as an adsorption group is even more preferred.
[0043] The low Tg (meth)acrylic acid ester (B2) means a (meth)acrylic acid ester (preferably a (meth)acrylic acid alkyl ester) whose homopolymer has a glass transition temperature of 0° C. or lower. Since the low molecular weight polymer (B) has a structural unit derived from the low Tg (meth)acrylic acid ester (B2), compatibility with the adhesive polymer is enhanced, and therefore the dispersion stability of the metal oxide particles (A) in the adhesive composition can be further improved.
[0044] Examples of the low Tg (meth)acrylic acid ester (B2) include the following: The numbers in parentheses indicate the glass transition temperatures of the homopolymers. Methacrylic acid C such as 2-ethylhexyl methacrylate (-10°C) 8-20 Alkyl esters; Acrylic acid C such as ethyl acrylate (-24°C), n-butyl acrylate (-54°C), 2-methoxyethyl acrylate (-50°C), n-octyl acrylate (-80°C), 2-ethylhexyl acrylate (-70°C), and isooctyl acrylate (-58°C) 2-20 Alkyl esters.
[0045] The low Tg (meth)acrylic acid ester (B2) may be used alone or in combination. As the low Tg (meth)acrylic acid ester (B2), acrylic acid C 2-20 The alkyl ester is preferred, and the alkyl group is branched.3-20 Alkyl esters are more preferred. In addition, two or more kinds of acrylic acid C 2-20 When combining alkyl esters, acrylic acid C with branched alkyl groups is used. 3-20 Alkyl ester (B2a) and acrylic acid C, in which the alkyl group is linear 3-20 It is preferable to combine with alkyl ester (B2b), and acrylic acid C 3-20 Alkyl ester (B2a) and acrylic acid C with linear alkyl groups 3-20 It is more preferable that the mass ratio (B2a / B2b) to the alkyl ester (B2b) exceeds 1.0.
[0046] The glass transition temperature of the homopolymer of the low Tg (meth)acrylic acid ester (B2) is preferably from -150 to -10°C, more preferably from -120 to -30°C, and even more preferably from -90 to -40°C.
[0047] The aromatic monomer (B3) has at least one aromatic hydrocarbon ring and at least one polymerizable unsaturated group in the molecule. The polymerizable unsaturated group may be a (meth)acryloyl group, a vinyl group, etc., among which a (meth)acryloyl group is preferred, and an acryloyl group is more preferred. The aromatic hydrocarbon ring may be a benzene ring, a naphthalene ring, a phenanthrene ring, an anthracene ring, etc., among which a benzene ring is preferred. When the low molecular weight polymer (B) contains a structural unit derived from an aromatic monomer (B3), the refractive index of the resulting pressure-sensitive adhesive can be increased, and preferably the refractive index can be increased while exhibiting high transparency.
[0048] Examples of the aromatic monomer (B3) include styrene monomers, aryl (meth)acrylates, aralkyl (meth)acrylates, aryloxy group-containing alkyl (meth)acrylates, and maleimides having an aryl group.
[0049] Examples of the styrene monomer include styrene, α-methylstyrene, p-methylstyrene, tert-butylstyrene, chlorostyrene, chloromethylstyrene, divinylbenzene, p-styryltrimethoxysilane, and 2-styrylethyltrimethoxysilane. Examples of the aryl (meth)acrylate include phenyl (meth)acrylate and naphthyl (meth)acrylate. Examples of the aralkyl (meth)acrylate include benzyl (meth)acrylate, methoxybenzyl (meth)acrylate, 2-phenoxybenzyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenylethyl (meth)acrylate, and naphthylmethyl (meth)acrylate. Examples of the aryloxy group-containing alkyl (meth)acrylate include phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, methylphenoxyethyl (meth)acrylate, and 2-naphthoethyl (meth)acrylate. An example of a maleimide having an aryl group is N-phenylmaleimide.
[0050] In particular, the aromatic monomer (B3) is preferably an aryl(meth)acrylate, an aralkyl(meth)acrylate, or an aryloxy group-containing alkyl(meth)acrylate, more preferably an arylacrylate or an aralkylacrylate, and particularly preferably an aralkylacrylate having an aryloxy group such as a phenoxy group on an aromatic hydrocarbon ring. When the aromatic monomer (B3) is the above compound, the resulting pressure-sensitive adhesive exhibits a high refractive index while also improving adhesion.
[0051] The aromatic monomer (B3) is preferably a monomer having a refractive index of 1.5 or more. By using such a monomer, the refractive index of the resulting adhesive can be further increased. The refractive index of the aromatic monomer (B3) is preferably 1.5 to 1.9, more preferably 1.53 to 1.8. The refractive index of the aromatic monomer (B3) can be measured using a multi-wavelength Abbe refractometer DR-M4 type (measurement temperature 20°C, interference filter wavelength 589 (D) nm) manufactured by ATAGO.
[0052] The low-molecular-weight polymer (B) may contain one or more types of structural units derived from an aromatic monomer (B3).
[0053] The other monomer (P) refers to a polymerizable monomer other than the monomer (B1) having an adsorption site for a metal oxide, the low Tg (meth)acrylic acid ester (B2), and the aromatic monomer (B3).
[0054] Examples of the monomer (P) include high Tg (meth)acrylic acid esters, such as methyl (meth)acrylate, ethyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate, whose homopolymers have a glass transition temperature higher than 0° C.; vinyl esters, such as vinyl acetate and vinyl propionate; and nitrile group-containing monomers, such as (meth)acrylonitrile.
[0055] In particular, the low molecular weight polymer (B) contained in the composition 1 contains a structural unit derived from an aromatic monomer (B3) from the viewpoint of increasing the refractive index of the resulting pressure-sensitive adhesive. The low molecular weight polymer (B) contained in the composition 1 is preferably a copolymer having a structural unit derived from an aromatic monomer (B3), a structural unit derived from a monomer (B1) having an adsorption site for a metal oxide, and / or a structural unit derived from a low Tg (meth)acrylic acid ester (B2), more preferably a copolymer having a structural unit derived from an aromatic monomer (B3) and a structural unit derived from a monomer (B1) having an adsorption site for a metal oxide, and even more preferably a copolymer having a structural unit derived from an aromatic monomer (B3), a structural unit derived from a monomer (B1) having an adsorption site for a metal oxide, and a structural unit derived from a low Tg (meth)acrylic acid ester (B2).
[0056] Furthermore, the low molecular weight polymer (B) contained in the composition 2 is preferably a (co)polymer having a structural unit derived from a monomer (B1) having a metal oxide adsorption site and / or a structural unit derived from a low Tg (meth)acrylic acid ester (B2), more preferably a (co)polymer containing at least a structural unit derived from a monomer (B1) having a metal oxide adsorption site, even more preferably a copolymer having a structural unit derived from a monomer (B1) having a metal oxide adsorption site and a structural unit derived from a low Tg (meth)acrylic acid ester (B2), and even more preferably a copolymer having a structural unit derived from a monomer (B1) having a metal oxide adsorption site, a structural unit derived from a low Tg (meth)acrylic acid ester (B2), and a structural unit derived from an aromatic monomer (B3).
[0057] The proportion of structural units derived from the monomer (B1) having an adsorption site for a metal oxide in 100% by mass of the low molecular weight polymer (B) is, for example, 0.1 to 20% by mass, preferably 1 to 15% by mass, and more preferably 2 to 10% by mass. By adjusting the proportion within the above range, the effect of suppressing the aggregation of the metal oxide particles (A) can be further improved.
[0058] The proportion (PB) of structural units derived from the low Tg (meth)acrylic acid ester (B2) in 100% by mass of the low molecular weight polymer (B) is, for example, 10 to 80% by mass, preferably 25 to 65% by mass, and more preferably 35 to 55% by mass. By adjusting it to the above range, the compatibility with the adhesive (meth)acrylic polymer (C) is improved.
[0059] The ratio of the structural units derived from the aromatic monomer (B3) in 100% by mass of the low molecular weight polymer (B) is, for example, 0 to 90% by mass, preferably 10 to 90% by mass, more preferably 20 to 80% by mass, and even more preferably 30 to 70% by mass. By setting the ratio to a predetermined value or more, the refractive index of the resulting pressure-sensitive adhesive can be further increased. In addition, by setting the ratio to a predetermined value or less, the compatibility of the low molecular weight polymer (B) with non-aromatic solvents and the adhesiveness of the resulting pressure-sensitive adhesive can be increased. In particular, in the composition 1, the proportion of structural units derived from the aromatic monomer (B3) in 100% by mass of the low molecular weight polymer (B) is 10 to 90% by mass, preferably 20 to 80% by mass, and more preferably 30 to 70% by mass. In the composition 2, the proportion of structural units derived from the aromatic monomer (B3) in 100% by mass of the low molecular weight polymer (B) is preferably 0 to 90% by mass, more preferably 10 to 90% by mass, even more preferably 20 to 80% by mass, and particularly preferably 30 to 70% by mass.
[0060] When the low-molecular-weight polymer (B) has structural units derived from a monomer (B1) having an adsorption site for a metal oxide and structural units derived from an aromatic monomer (B3), the content of the structural units derived from the monomer (B1) having an adsorption site for a metal oxide per 100 parts by mass of the structural units derived from the aromatic monomer (B3) is preferably 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 3 to 20 parts by mass. In addition, when the low-molecular-weight polymer (B) has a structural unit derived from a low Tg (meth)acrylic acid ester (B2) and a structural unit derived from an aromatic monomer (B3), the content of the structural unit derived from the low Tg (meth)acrylic acid ester (B2) per 100 parts by mass of the structural unit derived from the aromatic monomer (B3) is preferably 20 to 300 parts by mass, more preferably 40 to 200 parts by mass, and even more preferably 60 to 150 parts by mass.
[0061] In 100% by mass of structural units derived from polymerizable monomers constituting the low molecular weight polymer (B), the total content of structural units derived from monomer (B1) having a metal oxide adsorption site, structural units derived from low Tg (meth)acrylic acid ester (B2), and structural units derived from aromatic monomer (B3) is, for example, 60% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be 100% by mass.
[0062] It is also preferable that the low molecular weight polymer (B) is a polymer having a polar functional group at the end of the main chain. The low molecular weight polymer (B) contained in the composition 2 is a polymer having a polar functional group at the end of the main chain, but the low molecular weight polymer (B) contained in the composition 1 may also be a polymer having a polar functional group at the end of the main chain. By having a polar functional group at the end of the main chain, the low molecular weight polymer (B) is oriented on the surface of the metal oxide particle (A), and the dispersion stability of the metal oxide particle (A) in the dispersion composition or the pressure-sensitive adhesive composition is improved. In particular, it is preferable in that the dispersion composition or the pressure-sensitive adhesive composition can maintain good dispersibility even after storing it for a certain period of time (for example, 24 hours). Furthermore, by having a polar functional group at the end of the main chain, the compatibility with the organic solvent described later can also be improved. This improvement in dispersion stability and compatibility can increase the transparency of the obtained pressure-sensitive adhesive, and preferably can increase the transparency while showing a high refractive index.
[0063] Furthermore, when conventional polymer dispersants are used, if a solvent having a low content of aromatic hydrocarbon compounds, such as toluene or xylene, or containing no aromatic hydrocarbon compounds (hereinafter sometimes referred to as a non-aromatic solvent) is used as the organic solvent described below, there was a problem that aggregation of the metal oxide particles (A) occurs in the resulting dispersion composition or pressure-sensitive adhesive composition. However, by using a low molecular weight polymer (B) having a polar functional group at the end of the main chain, it is possible to provide a dispersion composition or pressure-sensitive adhesive composition having good dispersion stability, even in an embodiment in which such aggregation is likely to occur.
[0064] Examples of the polar functional group include an amino group, an amide group, a sulfo group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, a thiol group, an epoxy group, and an oxazoline group. Among them, an amino group, an amide group, a sulfo group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, a hydroxy group, and a thiol group are preferred, a carboxy group, a hydroxy group, an amino group, a sulfo group, a phosphoric acid group, a phosphonic acid group, and a hydrolyzable alkoxysilyl group are more preferred, a carboxy group, a sulfo group, a phosphoric acid group, a phosphonic acid group, and a hydrolyzable alkoxysilyl group are even more preferred, and a carboxy group is particularly preferred.
[0065] The low molecular weight polymer (B) having a polar functional group at the main chain terminal can be produced, for example, by using a chain transfer agent having a polar functional group and a group participating in a chain transfer reaction, such as a thiol group, in the polymerization step. That is, the low molecular weight polymer (B) having a polar functional group at the main chain terminal preferably has a structural unit derived from the chain transfer agent (B4) having a polar functional group.
[0066] Examples of the chain transfer agent (B4) having a polar functional group include chain transfer agents having a carboxy group, such as mercaptoacetic acid, 3-mercaptopropionic acid, and mercaptosuccinic acid; chain transfer agents having a hydroxy group, such as 2-mercaptoethanol and 3-mercapto-1,2-propanediol; chain transfer agents having an amino group, such as 2-aminoethanethiol; chain transfer agents having a sulfo group, such as 2-mercaptoethanesulfonate (e.g., sodium 2-mercaptoethanesulfonate); chain transfer agents having a phosphate group, such as mono(2-mercaptoethyl)phosphate; chain transfer agents having a phosphonic acid group, such as 3-mercaptopropylphosphonic acid; chain transfer agents having a hydrolyzable alkoxysilyl group, such as alkoxysilane compounds having a mercapto group, such as 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane; chain transfer agents having an amide group, such as mercaptoacetamide; and chain transfer agents having a thiol group, such as 1,6-hexanedithiol. The low-molecular-weight polymer (B) may contain one or more structural units derived from a chain transfer agent (B4) having a polar functional group.
[0067] The ratio of structural units derived from the chain transfer agent (B4) having a polar functional group in 100% by mass of the low molecular weight polymer (B) is, for example, 0 to 20% by mass, preferably 1 to 10% by mass, and more preferably 3 to 8% by mass. By making the ratio of structural units derived from (B4) a predetermined value or more, it is possible to further improve the dispersion stability of the dispersion composition or the pressure-sensitive adhesive composition and the compatibility with organic solvents (particularly non-aromatic solvents). In addition, by making the ratio of structural units derived from (B4) a predetermined value or less, it is possible to prevent the weight average molecular weight of the low molecular weight polymer (B) from becoming too small, and as a result, it is possible to further suppress the aggregation of the metal oxide particles (A).
[0068] From the viewpoint of further enhancing dispersion stability, the total proportion of the structural units derived from the monomer (B1) having a metal oxide adsorption site and the structural units derived from the chain transfer agent (B4) having a polar functional group is, for example, 1 to 30 mass%, preferably 2 to 20 mass%, and more preferably 3 to 15 mass%, in 100 mass% of the low molecular weight polymer (B). When the low-molecular-weight polymer (B) has structural units derived from an aromatic monomer (B3) and structural units derived from a chain transfer agent (B4) having a polar functional group, the content of the structural units derived from the chain transfer agent (B4) having a polar functional group per 100 parts by mass of the structural units derived from the aromatic monomer (B3) is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, and even more preferably 5 to 15 parts by mass.
[0069] In 100% by mass of the low molecular weight polymer (B), the total content of the structural units derived from the monomer (B1) having a metal oxide adsorption site, the structural units derived from the low Tg (meth)acrylic acid ester (B2), the structural units derived from the aromatic monomer (B3), and the structural units derived from the chain transfer agent (B4) having a polar functional group is, for example, 60% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and may be 100% by mass.
[0070] The content of the low molecular weight polymer (B) in the dispersion composition is, for example, 1 to 50 mass %, preferably 3 to 30 mass %, and more preferably 5 to 20 mass %.
[0071] The low molecular weight polymer (B) can be produced by a known method. For example, it can be obtained by polymerizing the above-mentioned polymerizable monomers (monomer (B1) having an adsorption site of a metal oxide, low Tg (meth)acrylic acid ester (B2), aromatic monomer (B3), and other monomers (P)). In addition, the polymerization may be carried out in the presence of a chain transfer agent such as a chain transfer agent (B4) having a polar functional group, if necessary. As the polymerization method, a known polymerization method can be adopted, and for example, a solution polymerization method, a bulk polymerization method, a suspension polymerization method, an emulsion polymerization method, etc. are mentioned. Among them, the solution polymerization method is preferable. The types, combinations, and compounding ratios of the polymerizable monomers and chain transfer agents used in each polymerization method are in accordance with the preferred forms described for the polymerizable monomers and chain transfer agents for forming the above-mentioned low molecular weight polymer (B). A preferred production method in the solution polymerization method will be described in detail below, but is not limited thereto.
[0072] Regarding the specific means and conditions for carrying out the solution polymerization method, means and techniques in the conventionally known solution polymerization method can be appropriately selected and adopted. For example, there is a method in which a polymerizable monomer is polymerized in the presence of an organic solvent, a polymerization initiator, and a chain transfer agent used as necessary.
[0073] Specific examples of the polymerization initiator include peroxide-based polymerization initiators such as methyl ethyl ketone peroxide, benzoyl peroxide, dicumyl peroxide, di-t-butyl peroxide, t-butyl hydroperoxide, cumene hydroperoxide, t-butyl peroxy octoate, t-butyl peroxy benzoate, and lauroyl peroxide; and azo-based polymerization initiators such as azobisisobutyronitrile, 2,2-azobis(2-methylbutyronitrile), 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(2-diaminopropane) hydrochloride, 4,4-azobis(4-cyanovaleric acid), and 2,2-azobis(2-methylpropionamidine). The polymerization initiator may be used alone or in combination of two or more kinds. The amount of the polymerization initiator is preferably 0.01 to 3 parts by mass with respect to 100 parts by mass of the polymerizable monomer.
[0074] Examples of the organic solvent include the organic solvents described below as organic solvents that can be contained in the dispersion composition, and the preferred embodiments thereof are the same. In particular, by using the organic solvent contained in the dispersion composition as the solvent during polymerization, the solution after the reaction can be used as is for preparing the dispersion composition, thereby simplifying the manufacturing process of the dispersion composition.
[0075] The amount of the organic solvent used may be appropriately determined depending on the reaction conditions, the composition of the polymerizable monomer, and the like so as to obtain a polymer having desired physical properties. For example, the amount of the organic solvent used is preferably 10 to 300 parts by mass, and more preferably 50 to 200 parts by mass, relative to 100 parts by mass of the polymerizable monomer.
[0076] The reaction conditions such as reaction temperature and reaction time in the solution polymerization method are not particularly limited, and can be appropriately determined depending on the composition of the polymerizable monomer and the properties required for the resulting polymer. The reaction temperature is, for example, 0 to 100°C, preferably 50 to 95°C, and more preferably 60 to 90°C, and the reaction time is, for example, 0.5 to 30 hours, preferably 1 to 20 hours, and more preferably 3 to 10 hours. The reaction pressure is also not particularly limited, and may be normal pressure (atmospheric pressure), reduced pressure, or increased pressure. The polymerization reaction is desirably carried out under an atmosphere of an inert gas such as nitrogen gas.
[0077] [Dispersant] The present invention also includes a dispersion composition obtained by further adding a dispersant to the above-mentioned metal oxide particles (A) and low molecular weight polymer (B). That is, the dispersion composition of the present invention may contain a dispersant other than the low molecular weight polymer (B) as necessary. By adding a dispersant, the dispersion stability of the metal oxide particles (A) in the dispersion composition or the pressure-sensitive adhesive composition can be further improved.
[0078] The dispersant may be any of the compounds described above as the surface treatment agent for the metal oxide particles (A). Among them, organic phosphorus compounds are preferred, and phosphates, phosphites and phosphonates having a polyether chain are more preferred.
[0079] The content of the dispersant is, for example, 0 to 35 parts by mass, preferably 1 to 30 parts by mass, and more preferably 5 to 25 parts by mass, relative to 100 parts by mass of the metal oxide particles (A). The content of the dispersant is, for example, 0 to 15 mass %, preferably 0.1 to 12 mass %, and more preferably 1 to 9 mass %, relative to 100 mass % of the dispersion composition.
[0080] [Organic solvents] The dispersion composition of the present invention may contain an organic solvent as necessary. The organic solvent may be derived from the solvent used during polymerization of the low molecular weight polymer, or may be added separately as a diluent. Examples of organic solvents include aliphatic hydrocarbon compounds such as n-hexane and n-heptane; alicyclic hydrocarbon compounds such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, ethylcyclohexane, diethylcyclohexane, decahydronaphthalene, bicycloheptane, tricyclodecane, hexahydroindenecyclohexane, cyclooctane, α-pinene, terpinolene, and limonene; aromatic hydrocarbon compounds such as toluene, xylene, benzene, and solvent naphtha; ester compounds such as ethyl acetate and butyl acetate; and ketone compounds such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Among them, at least one selected from aromatic hydrocarbon compounds and ester compounds is preferred, and ester compounds are more preferred.
[0081] The organic solvents may be used alone or in combination of two or more kinds.
[0082] In addition, aromatic hydrocarbon compounds such as toluene and xylene are harmful, so it is preferable to use an organic solvent that contains a small amount of aromatic hydrocarbon compounds such as toluene and xylene, or does not contain aromatic hydrocarbon compounds (i.e., a non-aromatic solvent). Therefore, from the viewpoint of toxicity, the content of aromatic hydrocarbon compounds (particularly toluene and xylene) is, for example, 50% by mass or less, preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, in 100% by mass of the organic solvent, and 1% by mass or less or 0% by mass is particularly preferred. Since the present invention uses a specific low molecular weight polymer (B), the content of toluene or xylene can show good dispersion stability at least, and the obtained adhesive can show good transparency and refractive index.
[0083] The content of the organic solvent is, for example, 0 to 800 parts by mass, preferably 15 to 500 parts by mass, and more preferably 30 to 300 parts by mass, per 100 parts by mass of the total of the metal oxide particles (A) and the low-molecular-weight polymer (B). The content of the organic solvent is, for example, 0 to 90 mass %, preferably 15 to 80 mass %, and more preferably 30 to 70 mass %, relative to 100 mass % of the dispersion composition. In addition, the content of aromatic hydrocarbon compounds (particularly toluene and xylene) is, for example, 70 mass% or less, preferably 30 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 1 mass% or less or 0 mass% in 100 mass% of the dispersion composition.
[0084] [Other ingredients] The dispersion composition of the present invention may contain other components as necessary, such as pigments, antioxidants, UV absorbers, and UV stabilizers.
[0085] <Adhesive composition> The present invention also includes a pressure-sensitive adhesive composition comprising the above-mentioned dispersion composition and an adhesive (meth)acrylic polymer (C).
[0086] [Dispersion composition] The dispersion composition contained in the PSA composition is as described above, and the preferred embodiments thereof are also the same.
[0087] The content of the dispersion composition in the pressure-sensitive adhesive composition is not particularly limited, but the amount of the metal oxide particles (A) in 100% by mass of the pressure-sensitive adhesive composition is, for example, 5 to 60% by mass, preferably 10 to 50% by mass, and more preferably 15 to 45% by mass. In the present invention, it is possible to blend metal oxide particles (A) having a refractive index of 2 or more at a high concentration, and for example, the amount of the metal oxide particles (A) in the pressure-sensitive adhesive composition can be 20 to 60% by mass.
[0088] The content of the low molecular weight polymer (B) in 100% by mass of the pressure-sensitive adhesive composition is, for example, 1 to 50% by mass, preferably 2 to 30% by mass, and more preferably 4 to 20% by mass.
[0089] [Adhesive (meth)acrylic polymer (C)] The adhesive (meth)acrylic polymer (C) is a homopolymer or copolymer of a low Tg (meth)acrylic acid ester (C2) having a glass transition temperature of the homopolymer of 0° C. or lower. Specific examples and preferred ranges of the low Tg (meth)acrylic acid ester (C2) are the same as those of the low Tg (meth)acrylic acid ester (B2) described above, and they may be used alone or in combination.
[0090] The proportion (PC) of structural units derived from the low Tg (meth)acrylic acid ester (C2) in 100 mass% of the adhesive (meth)acrylic polymer (C) is, for example, 5 to 100 mass%, preferably 10 to 80 mass%, more preferably 20 to 60 mass%.
[0091] In addition, the mass proportion (PC) of the low Tg (meth)acrylic acid ester (C2) unit in the adhesive (meth)acrylic polymer (C) contained in the adhesive composition is preferably close to the mass proportion (PB) of the low Tg (meth)acrylic acid ester (B2) unit in the low molecular weight polymer (B). When these mass proportions are close to each other, the affinity between the adhesive (meth)acrylic polymer (C) and the low molecular weight polymer (B) becomes good. The mass proportion (PB) of the low Tg (meth)acrylic acid ester (B2) unit in the low molecular weight polymer (B) is, for example, 0.3 to 3 times, preferably 0.5 to 2 times, more preferably 0.8 to 1.8 times the mass proportion (PC) of the low Tg (meth)acrylic acid ester (C2) unit in the adhesive (meth)acrylic polymer (C).
[0092] The adhesive (meth)acrylic polymer is preferably a copolymer of the low Tg (meth)acrylic acid ester (C2) and a polar group-containing monomer (C1). By copolymerizing the polar group-containing monomer (C1), the strength of the adhesive (meth)acrylic polymer can be increased.
[0093] The polar group-containing monomer (C1) may be a monomer having one or more polar groups selected from an amino group, an amide group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxyl group, a thiol group, an epoxy group, and an oxazoline group. Specific examples of the polar group-containing monomer (C1) are the same as those of the monomer (B1) having an adsorption site for a metal oxide described above, and may be used alone or in combination.
[0094] The polar group-containing monomer (C1) is preferably a monomer having one or more polar groups selected from an amino group, an amide group, a carboxy group, a phosphoric acid group, a phosphonic acid group, and a hydroxy group, more preferably a monomer having one or more polar groups selected from an amino group, an amide group, a carboxy group, and a hydroxy group, and particularly preferably a monomer having one or more polar groups selected from an amide group, a carboxy group, and a hydroxy group.
[0095] The proportion of the structural unit derived from the polar group-containing monomer (C1) in 100% by mass of the adhesive (meth)acrylic polymer (C) is, for example, 1 to 50% by mass, preferably 5 to 40% by mass, more preferably 10 to 30% by mass. From the viewpoint of further suppressing aggregation of the metal oxide particles (A), the proportion of the structural unit derived from the polar group-containing monomer in which the polar group is a carboxyl group is, for example, 0.1 to 20% by mass, preferably 0.5 to 10% by mass, more preferably 1 to 8% by mass. The content of the structural units derived from the polar group-containing monomer (C1) is, for example, 10 to 100 parts by mass, preferably 30 to 90 parts by mass, and more preferably 40 to 80 parts by mass, relative to 100 parts by mass of the structural units derived from the low Tg (meth)acrylic acid ester (C2).
[0096] The adhesive (meth)acrylic polymer (C) is preferably a copolymer of the low Tg (meth)acrylic acid ester (C2) and an aromatic monomer (C3), and is particularly preferably a copolymer of the low Tg (meth)acrylic acid ester (C2), a polar group-containing monomer (C1), and an aromatic monomer (C3). By copolymerizing the aromatic monomer (C3), the refractive index of the resulting adhesive can be further increased.
[0097] Specific examples and preferred ranges of the aromatic monomer (C3) are the same as those of the aromatic monomer (B3) described above, and they may be used alone or in combination.
[0098] The proportion of structural units derived from the aromatic monomer (C3) in 100% by mass of the adhesive (meth)acrylic polymer (C) is, for example, 10 to 90% by mass, preferably 20 to 70% by mass, and more preferably 30 to 60% by mass. The content of the structural units derived from the aromatic monomer (C3) is, for example, 30 to 300 parts by mass, preferably 50 to 250 parts by mass, and more preferably 100 to 200 parts by mass, per 100 parts by mass of the structural units derived from the low Tg (meth)acrylic acid ester (C2).
[0099] In 100 mass% of the adhesive (meth)acrylic polymer (C), the total content of the structural units derived from the low Tg (meth)acrylic acid ester (C2), the structural units derived from the polar group-containing monomer (C1), and the structural units derived from the aromatic monomer (C3) is, for example, 60 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, and may be 100 mass% or less.
[0100] The adhesive (meth)acrylic polymer (C) may be copolymerized with a monomer (Q) other than the low Tg (meth)acrylic acid ester (C2), the polar group-containing monomer (C1), and the aromatic monomer (C3). Examples of the monomer (Q) include the same monomers as those described above for the monomer (P).
[0101] The weight average molecular weight of the adhesive (meth)acrylic polymer (C) is, for example, 200,000 to 1,000,000, preferably 250,000 to 800,000, and more preferably 300,000 to 600,000.
[0102] The content of the adhesive (meth)acrylic polymer (C) in the adhesive composition is not particularly limited, but the adhesive (meth)acrylic polymer (C) is contained in an amount of, for example, 1 to 60 parts by mass, preferably 3 to 30 parts by mass, and more preferably 5 to 20 parts by mass, per 100 parts by mass of the total of the metal oxide particles (A) and the low molecular weight polymer (B).
[0103] [Organic solvents] The pressure-sensitive adhesive composition may contain an organic solvent as necessary. Specific examples and preferred aspects of the organic solvent are the same as those of the organic solvent in the dispersion composition, and may be used alone or in combination. The organic solvent contained in the pressure-sensitive adhesive composition may be an organic solvent derived from the dispersion composition, may be an organic solvent derived from the solvent used in polymerization of the adhesive (meth)acrylic polymer, or may be an organic solvent added as a diluent to the dispersion composition and the adhesive (meth)acrylic polymer (C).
[0104] As described above, aromatic hydrocarbon compounds such as toluene and xylene are harmful, so the lower the content, the better. Therefore, the content of aromatic hydrocarbon compounds (particularly toluene and xylene) is, for example, 50% by mass or less, preferably 30% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, particularly preferably 1% by mass or less or 0% by mass, based on 100% by mass of the organic solvent.
[0105] The content of the organic solvent in the pressure-sensitive adhesive composition is, for example, 0 to 600 parts by mass, preferably 20 to 450 parts by mass, and more preferably 40 to 300 parts by mass, per 100 parts by mass of the total of the metal oxide particles (A) and the low molecular weight polymer (B). The content of the organic solvent is, for example, 0 to 90 mass %, preferably 20 to 80 mass %, and more preferably 30 to 70 mass %, relative to 100 mass % of the pressure-sensitive adhesive composition. In addition, the content of aromatic hydrocarbon compounds (particularly toluene and xylene) is, for example, 70 mass% or less, preferably 30 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 1 mass% or less or 0 mass% in 100 mass% of the adhesive composition.
[0106] The total content of the dispersion composition, the adhesive (meth)acrylic polymer (C), and the organic solvent contained as necessary in 100% by mass of the adhesive composition is, for example, 60 to 100% by mass, preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 95 to 100% by mass.
[0107] [Crosslinking agent] The pressure-sensitive adhesive composition may contain a crosslinking agent as necessary. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy compounds, melamine compounds, metal chelate compounds, aziridine compounds, mercapto compounds, oxazoline compounds, etc., and are preferably metal chelate compounds, isocyanate-based crosslinking agents, etc., and are more preferably isocyanate-based crosslinking agents. Metal chelate compounds and isocyanate-based crosslinking agents, especially isocyanate-based crosslinking agents, are highly reactive with hydroxyl groups and are excellent crosslinking agents.
[0108] Examples of the isocyanate crosslinking agent include aromatic diisocyanates such as tolylene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylylene diisocyanate, and polymethylene polyphenyl isocyanate; aliphatic diisocyanates such as butane diisocyanate, pentane diisocyanate, hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate, lysine diisocyanate, and butylene diisocyanate; alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,4-cyclohexane diisocyanate, cyclopentylene diisocyanate, and isophorone diisocyanate; adduct polyisocyanate compounds; biuret polyisocyanate compounds; and polyisocyanate compounds having an isocyanurate ring.
[0109] Examples of the adduct polyisocyanate compound include "Sumidur L" (manufactured by Sumitomo Bayer Urethane Co., Ltd.); "Coronate L" and "Coronate HL" (both manufactured by Nippon Polyurethane Industry Co., Ltd. (currently Tosoh Corporation)); and "Takenate D101E" (manufactured by Mitsui Chemicals, Inc.). Examples of the biuret polyisocyanate compound include "Sumidur N" (manufactured by Sumitomo Bayer Urethane Co., Ltd.). Examples of the polyisocyanate compound having an isocyanurate ring include "Desmodur IL" and "Desmodur HL" (both manufactured by Bayer AG); "Coronate EH" and "Coronate HX" (both manufactured by Nippon Polyurethane Industry Co., Ltd. (currently Tosoh Corporation)); "Takenate D110N" and "Takenate D120N" (both manufactured by Mitsui Chemicals, Inc.).
[0110] The crosslinking agent is, for example, 0.01 to 40 parts by mass, preferably 0.1 to 30 parts by mass, and more preferably 0.5 to 25 parts by mass, calculated as the solid content of the crosslinking agent, relative to 100 parts by mass of the adhesive (meth)acrylic polymer (C).
[0111] [Other ingredients] The adhesive composition may contain other components as necessary. The other components include crosslinking accelerators (acid catalysts such as paratoluenesulfonic acid, phosphoric acid, hydrochloric acid, and ammonium chloride), tackifiers ((polymerized) rosin-based tackifiers, (polymerized) rosin ester-based tackifiers, terpene-based tackifiers, terpene phenol-based tackifiers, coumarone-based tackifiers, coumarone-indene-based tackifiers, styrene resin-based tackifiers, xylene resin-based tackifiers, phenol resin-based tackifiers, and petroleum resin-based tackifiers), fillers, pigments, antioxidants, ultraviolet absorbers, and ultraviolet stabilizers. The content of the other components may be appropriately adjusted depending on the type of the other components, and is, for example, 0.1 to 20% by mass, and preferably 0.1 to 10% by mass, in the adhesive composition.
[0112] The pressure-sensitive adhesive obtained from the pressure-sensitive adhesive composition of the present invention has an increased refractive index and / or transparency. For example, the refractive index of the pressure-sensitive adhesive composition of the present invention is preferably 1.55 or more, more preferably 1.59 or more, and even more preferably 1.60 or more. The upper limit of the refractive index is not particularly limited, but is, for example, 1.8 or less. It can be said that the higher the refractive index of the pressure-sensitive adhesive composition, the higher the refractive index of the resulting pressure-sensitive adhesive. The haze measured by the method in the Examples described later is preferably less than 10%, more preferably 5% or less, and further preferably 3% or less. The lower limit of the haze is not particularly limited, but is, for example, 0.01 or more.
[0113] The pressure-sensitive adhesive composition can be used as a pressure-sensitive adhesive for appropriately bonding an image display section, a light source section, a recording section, a polarizing plate, a retardation plate, an optical compensation film, a brightness enhancing film, a light diffusing film, a protective film, and the like in image display devices such as liquid crystal displays (LCDs), organic EL displays, and plasma display panels (PDPs) and optical discs. Furthermore, the pressure-sensitive adhesive can be processed into various product forms as required, such as pressure-sensitive adhesive sheets, pressure-sensitive adhesive labels, pressure-sensitive adhesive tapes, and double-sided tapes. EXAMPLES
[0114] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified as long as it satisfies the spirit of the invention, and all of these modifications are included in the technical scope of the present invention. In the following, "parts" refers to parts by mass unless otherwise specified.
[0115] The molecular weights of the polymers obtained in the following Production Examples were measured, and the dispersion compositions and pressure-sensitive adhesive compositions obtained in the Examples and Comparative Examples were evaluated as follows. (1) Molecular weight measurement The weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (ratio of weight average molecular weight to number average molecular weight, Mw / Mn) of the polymer were calculated by standard polystyrene conversion method using gel permeation chromatography (GPC). For GPC, a measuring device (product number: HLC-8220GPC, manufactured by Tosoh Corporation) was used. The values measured under the following measurement conditions were converted using standard polystyrene (manufactured by Tosoh Corporation), and the converted values were used as the weight average molecular weight (Mw) and number average molecular weight (Mn) of the measured polymer. Furthermore, the molecular weight distribution (Mw / Mn) was calculated from the ratio of the weight average molecular weight to the number average molecular weight. (Measurement conditions) Separation column: Tosoh Corporation, product number: TSKgel Super HZM-H Extraction solvent: tetrahydrofuran Flow rate: 0.35mL / min Injection volume: 10μL / time Sample concentration: 0.2% by weight
[0116] (2) Dispersion stability The dispersion compositions and pressure-sensitive adhesive compositions obtained in the Examples and Comparative Examples were visually observed and evaluated according to the following criteria. ○: Neither turbidity nor sedimentation was observed one day after mixing. △: At least one of white turbidity and sedimentation was observed one day after mixing. ×: At least one of white turbidity and sedimentation was observed immediately after mixing.
[0117] (3) Refractive index The refractive index of the adhesive compositions obtained in the Examples and Comparative Examples was measured under the following conditions. It can be said that the higher the refractive index of the adhesive composition, the higher the refractive index of the adhesive of the resulting adhesive sheet or the like. Equipment: ATAGO multi-wavelength Abbe refractometer DR-M4 Interference filter: Wavelength 589(D)nm Measurement temperature: 20℃
[0118] (4) Haze The haze was measured using a turbidity meter (NDH7000 manufactured by Nippon Denshoku Industries Co., Ltd.) for each sample obtained under the following pressure-sensitive adhesive sheet preparation conditions. The smaller the haze, the better the transparency.
[0119] [Adhesive sheet manufacturing conditions] The adhesive composition was applied onto a PET film having a thickness of 50 μm, and then dried for 3 minutes at a temperature of 80° C. The adhesive layer had a thickness of 25 μm. A release paper (manufactured by Toyobo Co., Ltd., product name: E-7002) was attached to the upper surface of the adhesive layer to obtain an adhesive sheet having an adhesive surface on one side.
[0120] Production Example 1 (Metal Oxide) A 2-ethylhexanoate zirconium mineral spirit solution (782 parts, 2-ethylhexanoate content of 44% by mass, manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd.) was mixed with pure water (268 parts). The resulting mixture was placed in an autoclave equipped with a stirrer, and the atmosphere in the autoclave was replaced with nitrogen gas. The mixture was then heated to 180°C and held at that temperature for 16 hours (pressure inside the autoclave was 0.94 MPa) to react and produce zirconium oxide particles. The mixture after the reaction was then taken out, and the precipitate that had accumulated at the bottom was filtered out and washed with acetone, and then dried. The dried precipitate (100 parts) was dispersed in toluene (700 parts), resulting in a cloudy solution. Next, as a purification step, the mixture was filtered again with a quantitative filter paper (manufactured by Advantec Toyo Co., Ltd., No. 5C) to remove coarse particles in the precipitate. Furthermore, the filtrate was concentrated under reduced pressure to remove the toluene, and white zirconium oxide nanoparticles (metal oxide 1) were recovered.
[0121] Measurement of number-average particle size using an electron microscope The number-average particle diameter of the zirconium oxide nanoparticles was measured by observing them with an ultra-high resolution field emission scanning electron microscope (Hitachi High-Technologies Corporation, S-4800). The zirconium oxide nanoparticles were observed at a magnification of 150,000 times, and the length of each of 100 random particles in the major axis direction was measured, and the average value was taken as the number-average particle diameter. The number-average particle diameter of the zirconium oxide nanoparticles measured with the electron microscope was 12 nm.
[0122] Production Example 2 (Low Molecular Weight Polymer) In a reaction vessel equipped with a cooling tube, a nitrogen gas inlet tube, a thermometer, a dropping funnel, and a stirrer, 156 parts of ethyl acetate, 50.0 parts of 3-phenoxybenzyl acrylate (hereinafter, POB-A; refractive index 1.566), 45.8 parts of 2-ethylhexyl acrylate (hereinafter, 2EHA), 4.2 parts of acrylic acid (hereinafter, AA), and 4.0 parts of mercaptopropionic acid (hereinafter, MPA) were placed, and then 0.5 parts of an azo polymerization initiator (manufactured by Nippon Hydrazine Kogyo Co., Ltd., product name: ABN-E) was added. The mixture was allowed to react for 6 hours at 85°C in a nitrogen gas atmosphere to obtain low molecular weight polymer solution 1 containing a low molecular weight polymer (low molecular weight polymer 1) with a solid content of 40% by mass and a weight average molecular weight of 4,000.
[0123] Production Example 3 (Low Molecular Weight Polymer) In a reaction vessel equipped with a cooling tube, a nitrogen gas inlet tube, a thermometer, a dropping funnel, and a stirrer, 162 parts of toluene, 62.0 parts of 2EHA, 30.0 parts of butyl acrylate (hereinafter, BA), 8.0 parts of AA, and 8.0 parts of normal dodecyl mercaptan (hereinafter, nDM) were placed, and then 0.5 parts of an azo polymerization initiator (manufactured by Nippon Hydrazine Kogyo Co., Ltd., product name: ABN-E) was added. The mixture was allowed to react for 6 hours at 80°C in a nitrogen gas atmosphere to obtain a low molecular weight polymer liquid 2 containing a low molecular weight polymer (low molecular weight polymer 2) with a solid content of 40 mass% and a weight average molecular weight of 4,000.
[0124] Production Example 4 (Adhesive (meth)acrylic polymer) In a reaction vessel equipped with a cooling tube, a nitrogen gas introduction tube, a thermometer, a dropping funnel and a stirrer, 85.2 parts of ethyl acetate, 48.0 parts of POB-A, 21.4 parts of 2EHA, 10.0 parts of BA, 17.5 parts of N-vinylpyrrolidone (hereinafter, NVP), 2.5 parts of AA, and 0.6 parts of 2-hydroxyethyl methacrylate (hereinafter, HEMA) were placed, and then 0.3 parts of azo polymerization initiator (manufactured by Nippon Hydrazine Kogyo Co., Ltd., product name: ABN-R) was placed. The mixture was allowed to react for 8 hours at 80°C in a nitrogen gas atmosphere to obtain an adhesive polymer solution 1 containing an adhesive (meth)acrylic polymer (adhesive polymer 1) having a solid content of 54% and a weight average molecular weight of 400,000.
[0125] Production Example 5 (Adhesive (meth)acrylic polymer) In a reaction vessel equipped with a cooling tube, a nitrogen gas inlet tube, a thermometer, a dropping funnel and a stirrer, 150 parts of ethyl acetate, 58.9 parts of 2EHA, 20.5 parts of BA, 20.0 parts of NVP and 0.6 parts of HEMA were placed, and then 0.3 parts of an azo polymerization initiator (manufactured by Nippon Hydrazine Kogyo Co., Ltd., product name: ABN-R) was added. The mixture was allowed to react for 8 hours at 80°C in a nitrogen gas atmosphere to obtain an adhesive polymer solution 2 containing an adhesive (meth)acrylic polymer (adhesive polymer 2) having a solid content of 40% and a weight average molecular weight of 400,000.
[0126] Example 1 Zirconium oxide nanoparticles (metal oxide 1), toluene, and low molecular weight polymer liquid 1 were mixed in a mass ratio of metal oxide 1 / toluene / low molecular weight polymer liquid 1 / =25.0 / 40.7 / 25.0, and stirred until uniform to obtain dispersion composition 1. This dispersion composition 1 and adhesive polymer liquid 1 were mixed in a mass ratio of dispersion composition 1 / adhesive polymer liquid 1=90.7 / 9.3, and stirred until uniform to prepare adhesive composition 1. The composition of the obtained adhesive composition is shown in Table 1.
[0127] Example 2 Zirconium oxide nanoparticles (metal oxide 1), ethyl acetate, and low molecular weight polymer liquid 1 were mixed and stirred at a mass ratio of metal oxide 1 / ethyl acetate / low molecular weight polymer liquid 1 = 30.0 / 45.0 / 25.0 to prepare dispersion composition 2. The composition of the obtained dispersion composition is shown in Table 1.
[0128] Example 3 Zirconium oxide nanoparticles (metal oxide 1), ethyl acetate, and low molecular weight polymer liquid 1 were mixed and stirred at a mass ratio of metal oxide 1 / ethyl acetate / low molecular weight polymer liquid 1 = 24.0 / 38.3 / 27.5 to obtain dispersion composition 3. This dispersion composition 3 and adhesive polymer liquid 1 were mixed at a mass ratio of dispersion composition 3 / adhesive polymer liquid 1 = 89.8 / 10.2 and stirred until homogenous, to prepare adhesive composition 3. The composition of the obtained adhesive composition is shown in Table 1.
[0129] Comparative Example 1 Zirconium oxide nanoparticles (metal oxide 1), toluene, and low molecular weight polymer liquid 2 were mixed in a mass ratio of metal oxide 1 / toluene / low molecular weight polymer liquid 2 / =25.0 / 37.5 / 25.0, and stirred until uniform to obtain dispersion composition 4. This dispersion composition 4 and adhesive polymer liquid 2 were mixed in a mass ratio of dispersion composition 4 / adhesive polymer liquid 2=87.5 / 12.5, and stirred until uniform to obtain adhesive composition 4. The composition of the obtained adhesive composition is shown in Table 1.
[0130] Comparative Example 2 Dispersion composition 5 was prepared in the same manner as in Example 2, except that the low molecular weight polymer liquid 1 was changed to the low molecular weight polymer liquid 2. The composition of the obtained dispersion composition is shown in Table 1.
[0131] Comparative Example 3 A pressure-sensitive adhesive composition 6 was prepared in the same manner as in Example 3, except that the low-molecular-weight polymer liquid 1 was changed to the low-molecular-weight polymer liquid 2. The composition of the resulting pressure-sensitive adhesive composition is shown in Table 1.
[0132] The properties of the dispersion compositions and pressure-sensitive adhesive compositions obtained in the Examples and Comparative Examples were examined, and the results are shown in Table 1.
[0133] [Table 1]
[0134] The dispersion composition containing the low molecular weight polymer of the present invention has good dispersion stability (Example 2), and the dispersion stability of the adhesive composition obtained by adding the dispersion composition containing the low molecular weight polymer of the present invention to an adhesive polymer is also good (Examples 1 and 3). In addition, the adhesive sheet obtained from such an adhesive composition has good refractive index and transparency (Examples 1 and 3). In particular, even if the toluene content is low or not included, it is preferable in that the dispersion stability, refractive index, and transparency are good.
Claims
1. The composition comprises metal oxide particles (A) and a polymer (B) having a weight average molecular weight of 50,000 or less, The polymer (B) contains 10 to 90 mass % of structural units derived from an aromatic monomer.
2. The composition according to claim 1 , wherein the aromatic monomer has a refractive index of 1.5 or greater.
3. The composition according to claim 1 , wherein the aromatic monomer is at least one monomer selected from the group consisting of aryl (meth)acrylates and aralkyl (meth)acrylates.
4. The composition according to claim 1, wherein the polymer (B) has at least one polar functional group selected from an amino group, an amide group, a sulfo group, a carboxy group, a phosphoric acid group, a phosphonic acid group, a hydrolyzable alkoxysilyl group, an isocyanate group, a hydroxy group, a thiol group, an epoxy group, and an oxazoline group.
5. The composition according to claim 1 , wherein the polymer (B) further contains a structural unit derived from a low Tg (meth)acrylic acid ester such that the glass transition temperature of the homopolymer is 0° C. or lower.
6. The composition according to claim 1, wherein the content of the metal oxide particles (A) is 100 to 450 parts by mass based on 100 parts by mass of the polymer (B).
7. The present invention comprises metal oxide particles (A) and a polymer (B) having a weight average molecular weight of 50,000 or less, The composition, wherein the polymer (B) is a polymer having a polar functional group at an end of the main chain.
8. 8. The composition according to claim 7, wherein the polar functional group is a functional group selected from a carboxyl group, a hydroxyl group, an amino group, a sulfo group, a phosphoric acid group, a phosphonic acid group, and a hydrolyzable alkoxysilyl group.
9. The composition according to claim 7, wherein the polymer (B) further contains a structural unit derived from a low Tg (meth)acrylic acid ester such that the glass transition temperature of the homopolymer is 0°C or lower.
10. The composition according to claim 7, wherein the content of the metal oxide particles (A) is 100 to 450 parts by mass based on 100 parts by mass of the polymer (B).
11. The composition according to claim 1 or 7, wherein the metal oxide particles (A) have a refractive index of 2 or more.
12. The composition according to claim 1 or 7, wherein the content of toluene and xylene in the composition is 5 mass% or less.
13. A pressure-sensitive adhesive composition comprising the composition according to claim 1 or 7 and an adhesive (meth)acrylic polymer.
Citation Information
Patent Citations
Transparent adhesive for refractive index regulating optical member, transparent adhesive layer for optics, manufacturing method of transparent adhesive for refractive index regulating optical member and manufacturing method of transparent adhesive layer for optics
JP2009120726A
Adhesive composition
JP2021134322A
